Local Community Development through community-based tourism management: a Case Study of Mae Kampong Village - Jitpakdee, Pit; Harun, Azhar; Mohd. Zain, Zawiyah (MCSER Publishing, Rome-Italy, 2016)
The growth in tourism sector in Thailand is increasing rapidly over the past decades. Despite the conventional tourism that has reputation globally, another type of tourism is also growing in Thailand. With the assistance from scholar , public and private organizations, the non-governmental agencies, governmental officials and environmentalist, the community-based tourism (CBT) has become and alternative for tourist who would like to experience the local ways of live. Many communities tried to operate the CBT, however there were struggled by the poor management, and failed to be successful. The paper explores the context of the CBT in Thailand, analyze the CBT management of the case study of the village called Mae Kampong located in Chiang Mai, the province in the Northern part of Thailand, and extracts the important management strategist that made the village successful on the CBT operation. Collecting data, observing the phenomena in the village, and reviewing literatures for information and knowledgeon the management of Mae Kampong, this paper argues that the success of Mae Kampong Village is based upon the management system, the local participation, and the income distribution system